Fundos de investimento e a adesão na contratação digital - Silva, João Luiz Frossard Pestana da (2019)
When a client invests for the first time in a mutual fund, she must sign the document of adhesion and risk awareness. Considering this, the present investigation aimed to verify whether such a document is a valid instrument of proof in court even when it was electronically signed in divergence to the standard set by the ICP-BR rules. It was found that such a signature would be effective in proving the investor's identity if this way of identification has been previously agreed between the parties. This agreement could be tacit if the investor uses that signature continually to identify himself. Besides that, a technical expert could also demonstrate the veracity of the signature and the integrity of the document. Such a document is effective proof in court. Another aspect investigated regards the fact that the mutual fund administrator provides the bylaws and other information concerning the investment characteristics and risks so that the client could read it. It was found that just providing information for reading does not meet the law when dealing with retail investors. Consumer law protects these investors and requires that the mutual fund administrator take a proactive approach to educate them regarding the investment characteristics and risks